Pathological characterization of lung fibrosis in Sprague–Dawley rats treated with fluoro-edenite fibres by intrapleural injection - Eva Tibaldi; Federica Gnudi; Daniele Mandrioli; Caterina Bruno; Amerigo Zona; Lucia Fazzo; Pietro Comba (Journal of Occupational Medicine and Toxicology)
Abstract Background An increased incidence of pleural mesotheliomas in Biancavilla (Italy) was attributed to the environmental exposure to fluoro-edenite (FE). Results from the Ramazzini Institute (RI) in vivo long-term study confirmed the evidence that exposure to FE fibres is correlated with an increase of malignant pleural mesotheliomas in Sprague–Dawley rats. Recently asbestosis-like features were substantiated in Biancavilla residents without known occupational exposures. Aim of this work was to establish whether FE induce lung fibrosis with a pathogenetic mechanism similar to other asbestiform fibres. Methods Original slides from the RI study were systematically re-examined to characterize the FE-induced lesions. Quantitative analysis of lung fibrosis was assessed following the Ashcroft method. Immunohistochemical analysis of protein involved in fibrotic responses and histochemical staining for FE-fibres identification were performed. Results Like asbestos, FE caused fibrotic lesions, pleural plaques or nodules and mesotheliomas. A significant increase of lung fibrosis (p < 0.001) was observed in the FE-treated groups compared to untreated controls. In the fibrotic responses to FE, vimentin was the most expressed protein, followed by collagen-I and alpha-SMA. Finally, ferruginous bodies, characterized by iron deposits and ferritin expression, were observed in FE-induced lesions. Conclusions This study confirmed that FE exposure promotes the onset of fibrotic lesions at pleural level, as fibrous plaques or nodules and fibrosis, through a mechanism similar to other form of asbestos. These results combined with epidemiological study reported in Biancavilla residents, corroborate the need to promote health and epidemiological surveillance plans of respiratory diseases in population living in FE contaminated sites.